A New Risk Score for Patients With Acute Chest Pain and Normal High Sensitivity Troponin - Ma, Chunpeng; Liu, Xiaoli; Ma, Lixiang (Frontiers in Medicine, 2022)
Objective: To investigate a new risk score for patients who suffered from acute chest pain with normal high-sensitivity troponin I (hs-TnI) levels. Methods: In this study, patients with acute chest pain who were admitted to the emergency department (ED) of our hospital had been recruited. Hs-TnI was measured in serum samples drawn on admission to the emergency department.The end point was the occurrence of major adverse cardiac events within three months. Predictor variables were selected by logistic regression analysis and external validity was assessed in this study. Furthermore, validation was performed in an independent cohort including 352 patients (validation cohort). Results: A total of 724 patients were included in the derivation cohort. The results showed that four predictor variables were significant in the regression analysis—male, a history of chest pain, 60 years of age or older and with three or more CAD risk factors. A total of 105 patients in the validation cohort had serious adverse cardiac events. The validation cohort showed a homogenous pattern with the derivation cohort when patients were stratified by score. The area under curve (AUC) of the receiver operating characteristic (ROC) in the derivation cohort was 0.80 (95% CI: 0.76–0.83), while in the validation cohort, it was 0.79 (95% CI: 0.75–0.82). Conclusion: A new risk score was developed for acute chest pain patients without known CAD and ST-segment deviation and with normal hs-TnI and may aid MACE risk assessment and patient triage in the ED.